Associations of working from home with job satisfaction, work-life balance, and working-model preferences - Orešković, Tin; Milošević, Milan; Košir, Bruna Kostelac; Horvat, Darko; Glavaš, Tomislav; Sadarić, Antonio; Knoop, Carin-Isabel; Orešković, Stjepan (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic forced many businesses to shift towards remote and hybrid working models. This study explored the association of the work-from-home model with employee satisfaction, work-life balance, and work-model preferences within MPlus Group, a leader in telework within the business process and technology outsourcing (BPTO) industry. Methods We analyzed survey responses of 4,554 employees of MPlus Group across seven countries to assess the associations of working from home with job satisfaction, work-life balance, and preference regarding continuing to work from home. Results Employees working within all models, and both women and men, reported high levels of job satisfaction and work-life balance, and most employees working from home expressed a desire to continue doing so. Discussion Our findings suggest working from home does not lead to lower job satisfaction or work-life balance in the BPTO and similar industries. The study provides insights for organizations and policymakers navigating post-pandemic work dynamics. However, further research is needed to examine the long-term implications of remote work across diverse industries.